Ultrasound-measured ribeye area EPD for Brangus cattle - Schalles, R.R.; Glaze, J.B.; Mallen-Spinzi, R.; Andries, K.M.; Rost, C.J.; Johnson, M.Z.; Olson, W.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ultrasound-measured ribeye area (REA) expected progeny differences (EPD) were calculated for 2974 Brangus cattle. Carcass data were collected from 168 steer progeny sired by eight bulls with ultrasound-measured ribeye area EPDs. A heritability estimate of .40 for ultrasound-measured REA and a 2.82 sq. in. range in genetic differences in ultrasound- measured REAs in this population indicate considerable opportunity to make genetic change in this trait. The regression of progeny average carcass REA on the sire's ultrasound measured ribeye area EPD indicated that for each square inch change in the EPD, the carcass REA of their progeny changed by .69 sq. in. The ultrasound-measured ribeye area EPD of young breeding stock appears to be a reasonably good predictor of their progeny's carcass ribeye area.
Keywords: Beef; Ultrasound; Ribeye area EPD; Brangus cattle